Optimising Human Resource Information Systems in the Context of MSME Technology Management - Gani, Nurjaya; Degdo Suprayitno; Diky Wardhani; Hamzah Al Imran; Kusuma Agdhi Rahwana (Jurnal Informasi dan Teknologi, 2024)
This research explores the implementation of the Human Resource Information System (HRIS) in managing MSMEs, aiming to enhance operations and business development. The focus includes understanding the challenges of HRIS implementation, flexible workforce management strategies, and the benefits of adopting current technology. This research is hoped to provide valuable insights for MSMEs in leveraging HRIS for their business growth and efficiency. The research methodology used is survey design. Data was collected through a survey instrument consisting of scales to gather quantitative responses from business owners. The population of this study includes all entrepreneurs in Makassar, South Sulawesi, Indonesia, both those who have participated in government empowerment programs and those who have not. A purposive sampling technique was used to select 75 participants based on various criteria such as business type and background. The research findings affirm that optimizing HRIS in MSMEs can improve efficiency, productivity, and organizational performance. Technology-based HRM strategies, such as cloud-based software, mobile applications, and web-based platforms, can streamline HR processes and enhance workforce productivity. Human resource competencies play a crucial role in MSME development, and leveraging HRIS can optimize product and service marketing, contributing to MSME growth. The research emphasizes the importance of optimizing HRIS in MSME management. The results indicate that technology-based HRIS usage can enhance operational efficiency and workforce productivity. It is recommended that MSMEs invest in the latest HRIS technology and provide adequate employee training. These steps will support the growth and success of MSMEs in the current digital era.